Nucleotide and amino acid sequences of pulmonary surfactant protein SP 18 and evidence for cooperation between SP 18 and SP 28-36 in surfactant lipid adsorption. - Hawgood, S (1987)
Pulmonary surfactant is a lipid-rich material that promotes alveolar stability by lowering the surface tension at the air-fluid interface in the peripheral air spaces. The turnover of surfactant phospholipids in the alveolar space is fast, and several lines of evidence suggest there is rapid formation and replenishment of the phospholipid surface film during normal respiration. Specific proteins may regulate these dynamic surface properties. The predominant surfactant protein is a well-characterized, lipid-associated glycoprotein, SP 28-36 (28-36 kDa). A second group of very hydrophobic proteins has recently been shown to affect the surface activity of surfactant phospholipids. We have isolated this group of hydrophobic proteins, herein called SP 5-18 (5-18 kDa), from canine surfactant and have shown by NH2-terminal sequence analysis that at least two proteins, SP 5-8 and SP 18, are present in this group. We have derived the full amino acid sequence of SP 18 from the nucleotide sequence of the cDNAs identified with oligonucleotide probes that were based on the NH2-terminal amino acids of SP 18. The protein isolated from extracellular surfactant appears to be a fragment of a much larger precursor protein (40 kDa). The amino acid sequence of SP 18 is markedly hydrophobic and contains two possible bilayer-spanning domains. We have shown that SP 18 and the glycoprotein SP 28-36 have a cooperative, calcium-dependent action in promoting the formation of phospholipid surface films.